PENGARUH PEMBERIAN SANKSI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MELALUI DISIPLIN BELAJAR PADA SISWA KELAS X DI SMK NEGERI 7 MEDAN - Joice Carmelita Gultom; Sondang Aida Silalhi; Jufri Darma; Roza Thohiri; Andri Zainal (Jurnal Manajemen Pendidikan, 2026)
This study aimed to analyze the effect of punishment and learning motivation on learning outcomes through learning discipline as a mediating variable among tenth-grade Accounting students at SMK Negeri 7 Medan. The study employed a quantitative approach with a descriptive design involving 209 students selected using the total sampling technique. Data were collected through Likert-scale questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results showed that punishment did not significantly affect learning outcomes, indicated by a coefficient value of 0.106 and p-values of 0.150. In contrast, learning motivation had a positive and significant effect on learning outcomes with a coefficient value of 0.276 and p-values of 0.000. Punishment and learning motivation also had positive and significant effects on learning discipline, with coefficient values of 0.436 and 0.350, respectively. Furthermore, learning discipline significantly affected learning outcomes and mediated the relationship between punishment, learning motivation, and learning outcomes. The novelty of this study lies in the placement of learning discipline as a mediating variable in explaining the relationship between punishment, learning motivation, and learning outcomes among vocational high school students, particularly in accounting education.